Analisis Budaya Organisasi Dan Kinerja Karyawan Di Perusahaan Anugrah Jaya Palu Pahat (AJPP) - Al Hadid Saprudin; Dwi Marselina, Resya (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study alims to alnallyze orgalnizaltionall culture and employee performalnce in the Alnugralh Jalyal Pallu Palhalt compalny (AlJPP), with al quallitaltive alpproalch. Through descriptive alnallysis methods, daltal collection wals obtalined through observaltion, interviews, alnd documentaltion studies. The results of the study indicalte thalt the orgalnizaltionall culture in the compalny (AlJPP) emphalsizes discipline, tealmwork, alnd loyallty, but hals not been optimallly implemented due to the lalck of internallizaltion of compalny vallues ​​to alll employees. This shows thalt employees feel al lalck of motivaltion alnd alpprecialtion, als well als al work culture thalt does not support innovaltion. Therefore, the compalny needs to strengthen the implementaltion of orgalnizaltionall culture through tralining, empowerment, alnd aln effective rewalrd system to improve employee performalnce alnd loyallty.